Evaluating the Effectiveness of Bilingual Programs in Enhancing Non-English Subject Learning among Junior High School Students - Saputri, Maulidarni; Fathurrahman, M. Syauqi (Journal of Language and Literature Studies, 2025)
This study was carried out to investigate the effectiveness of bilingual programs in non-English learners and to identify the factors that contribute to their success. The research was conducted at Bunga Matahari International School, involving a sample of 27 junior high school students selected from a population of 65 using Slovin’s formula (1960). A quantitative descriptive approach was employed, utilizing documentation of students’ assessment scores and a questionnaire to evaluate factors influencing the success of the bilingual program. To assess program effectiveness, the researcher used descriptive statistics and a paired t-test to compare two sets of assessment scores provided by the school. The findings revealed significant improvements in Mathematics and Science, with Mathematics increasing from a mean score of 88 to 91 (p = 0.002), and Science from 90 to 94 (p = 0.000). In contrast, Social Studies showed only a minimal improvement, from 92 to 93, which was not statistically significant (p = 0.749). Key contributing factors to program success included the teacher’s role (87%), student engagement (80%), school support (74%), and learning resources (64%). These results suggest that teacher involvement and student engagement are critical to the success of bilingual programs. Future bilingual curriculum development and teacher training initiatives should prioritize enhancing these areas while also strengthening institutional support and access to adequate learning resources.